Network traffic control using traffic shaping techniques - Radojičić Valentina D.Ž.; Marković Goran Z.; Mitrović Slobodan D. (Tehnika)
Although known for years, the problem of meeting network traffic demand in multiservice environment is still recognized as one of the most significant challenges, regardless of the constant increase in network infrastructure capacity. One of the most important causes of this problem is the bursty nature of network traffic that could reflect on the network efficiency reduction due to temporal congestion of network resources. In this way, the operational characteristics of certain business systems as well as the quality of residential internet/iptv services could be compromised. One of the standard approaches to solving such a kind of problems is related to the concept of traffic management that includes 1) Traffic Policing techniques, as well as 2) Traffic Shaping techniques. Although these techniques share the same conceptual basis, these techniques also have significant differences, due to which they achieve different effects on network traffic. The importance of Traffic Shaping techniques arise with their potential to manage the traffic quality in modern network forms, such as Internet of Things (IoT) sensor networks. This paper explains the basic concept of traffic shaping, available algorithms on which traffic shaping techniques are based and provides a comparison with Traffic Policing techniques.